ANALISIS RESIDU BEKAS PAKAI: PROSEDUR DAN MANFAATNYA UNTUK PENELITIAN ARKEOLOGI DI KALIMANTAN - Nia Marniati Etie Fajari (Balai Arkeologi Kalimantan Selatan, 2008)
Microscopic analysis on traces of deposits on tools, either residue analysis or use-wear analysis, may provide information on technological characteristic, function, and types of use-wear of an artifact, which will further explain pattern of subsistence, exploiting plants and technology. Unfortunately, such analysis is still rarely used in an archaeological research in Kalimantan. This article discusses the advantages and prospect of benefiting microscopic analysis in archaeological researches in Kalimantan.